In Vivo Pharmacodynamic Characterization of Anidulafungin in a Neutropenic Murine Candidiasis Model - Andes, D. (American Society for Microbiology (ASM), 2008)
Multiple in vivo studies have characterized the pharmacodynamics of drugs from the triazole and polyene antifungal drug classes. Fewer studies have investigated these pharmacodynamic relationships for the echinocandin drug class. We used a neutropenic murine model of disseminated Candida albicans, Candida tropicalis, and Candida glabrata infection to characterize the time course of activity of the new echinocandin anidulafungin. The pharmacokinetic-pharmacodynamic (PK-PD) indices (the percentage of time that the drug concentration was above the MIC, the ratio of the area under the concentration-time curve from 0 to 24 h [AUC(0-24)] to the MIC, and the ratio of the maximum serum drug concentration [C(max)] to the MIC) were correlated with in vivo efficacy, as measured by organism numbers in kidney cultures after 96 h of therapy. The kinetics following intraperitoneal anidulafungin dosing in neutropenic infected mice were monitored. Peak levels and AUCs were linear over the 16-fold dose range studied. The drug elimination half-life in serum ranged from 14 to 24 h. Single-dose postantifungal-effect studies demonstrated prolonged suppression of organism regrowth after serum anidulafungin levels had fallen below the MIC. Of the four dosing intervals studied, treatment with the more widely spaced dosing regimens was most efficacious, suggesting the C(max)/MIC ratio as the PK-PD index most predictive of efficacy. Nonlinear regression analysis suggested that both the C(max)/MIC and AUC/MIC ratios were strongly predictive of treatment success. Studies were then conducted with 13 additional C. albicans, C. tropicalis, and C. glabrata isolates with various anidulafungin susceptibilities (MICs of anidulafungin for these strains, 0.015 to 2.0 μg/ml) to determine if similar C(max)/MIC and AUC(0-24)/MIC ratios for these isolates were associated with efficacy. The anidulafungin exposures associated with efficacy were similar among Candida species.